Ownership Structure and Foreign Commissioners for Human Resources Accounting Disclosures - Nova Maulud Widodo; Ari Kuncara Widagdo; Doddy Setiawan (The Indonesian Journal of Accounting Research, 2017)
Abstract: This study aims to examine the influence of foreign ownership, family ownership as well as the existence of foreign board commissioner on the human resource accounting disclosure (HRAD). This research uses the control variable, which are SIZE, CAR, LDR, and AGE. This study uses secondary data obtained from the Indonesia Stock Exchange (BEI). HRA disclosure was measured using the Mamun index. The research sample are banking company that listed in BEI period 2011-2014 chosen by purposive sampling method. The total annual report of the company used for the analysis was 133 reports. This research uses panel data with fixed effect test. Data analysis methods in the study using multiple linear regression. The ownership structure (foreign ownership and family ownership) are classified the percentage ownership of 20%, 30%, and 50%. The third independent variable is the foreign board of commissioners. The result of foreign ownership measurement at an ownership level> 20% and> 30% do not affect. Otherwise, foreign ownership at ownership level> 50% shows a negative influence on HRA disclosure. Family ownership measuring> 20% has a negative impact on HRA disclosure at 10% significance while using> 30% and 50% measurements does not affect. The existence of a foreign board of commissioners positively influences the disclosure of HRA. Control variables in this research that is SIZE and AGE have positive impact on HRA disclosure. While the CAR has no effect and the LDR negatively affects the 10% significance of HRA disclosure. In conclusion the higher the ownership will lead to the ultimate shareholder company. This affects the relationship to information disclosure.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh kepemilikan asing, kepemilikan keluarga serta keberadaan dewan komisaris asing pada pengungkapan akuntansi sumber daya manusia (HRAD). Penelitian ini menggunakan variabel kontrol, yaitu SIZE, CAR, LDR, dan AGE. Penelitian ini menggunakan data sekunder yang diperoleh dari Bursa Efek Indonesia (BEI). Pengungkapan HRA diukur menggunakan indeks Mamun. Sampel penelitian adalah perusahaan perbankan yang terdaftar di BEI periode 2011-2014 yang dipilih dengan metode purposive sampling. Total laporan tahunan perusahaan yang digunakan untuk analisis adalah 133 laporan. Penelitian ini menggunakan data panel dengan uji fixed effect. Metode analisis data dalam penelitian menggunakan regresi linier berganda. Struktur kepemilikan (kepemilikan asing dan kepemilikan keluarga) diklasifikasikan kepemilikan persentase 20%, 30%, dan 50%. Variabel independen ketiga adalah dewan komisaris asing. Hasil pengukuran kepemilikan asing pada tingkat kepemilikan> 20% dan> 30% tidak berpengaruh. Jika tidak, kepemilikan asing pada tingkat kepemilikan> 50% menunjukkan pengaruh negatif pada pengungkapan HRA. Pengukuran kepemilikan keluarga> 20% memiliki dampak negatif pada pengungkapan HRA pada tingkat signifikansi 10% sementara menggunakan> 30% dan pengukuran 50% tidak berpengaruh. Keberadaan dewan komisaris asing secara positif mempengaruhi pengungkapan HRA. Variabel kontrol dalam penelitian ini yaitu SIZE dan AGE memiliki dampak positif pada pengungkapan HRA. Sementara CAR tidak berpengaruh dan LDR berpengaruh negatif terhadap 10% signifikansi pengungkapan HRA. Kesimpulannya semakin tinggi kepemilikan akan menyebabkan perusahaan pemegang saham utama. Ini mempengaruhi hubungan untuk pengungkapan informasi.